Proficiency Skills Needed by Teachers for Optimal Performances in Motor Vehicle Mechanics Work in Technical Colleges in Adamawa and Taraba States - Obadiah, Yusuf Andy; Kumazhege, Stephen Z.; Aliyu, Yelwa (Lembaga Yasin AlSys, 2024)
The main purpose of the study was to determine the proficiency skills needed by teachers for optimal performances in motor vehicle mechanics work in technical colleges in Adamawa and Taraba States. The study was guided by two research questions and two null hypotheses. The study which adopted descriptive survey research design was conducted in Adamawa and Taraba States. The population of the study was 123 respondents comprising 81 MVMW teachers and 42 instructors from all the 21 BEST Centres and Government Science and Technical colleges in Adamawa and Taraba States, Nigeria. There was no sampling as the entire population was used because it was manageable. A structured questionnaire tagged: Proficiency Skills Needs of Motor Vehicle Mechanics Works Teachers Questionnaire (PSNMVMWTQ) was validated by three experts. The Instrument was trial tested in Gombe State and the Cronbach Alpha reliability method was used to test the reliability of the instrument and a 0.84 reliability coefficient was obtained. Data collected for the study was analyzed using Statistical Package for Social Sciences (SPSS) version 27.0. Mean statistics was used to answer the two research questions while a t-test was used to test the null hypotheses at a 0.05 level of significance. The findings of the study revealed among others that 35 technical skills were considered needed by MVMW teachers. Similarly, 25 ICT skills were considered as ‘needed’. Importantly, there were no significant differences between instructors and MVMW teachers regarding the perceived importance of these skills. It is recommended that to address the technical skills gaps identified, particularly in the use of diagnostic tools and performing necessary repairs, it is recommended that the Technical College Management Board should organize workshops and practical training sessions. These initiatives should emphasize hands-on experience with diagnostic equipment, connecting tools appropriately, and interpreting trouble codes.